Expression of MUC1, Thomsen-Friedenreich antigen, Tn, sialosyl-Tn, and α2,6-linked sialic acid in hepatocellular carcinomas and preneoplastic hepatocellular lesions - Cao, Yi; Bannasch, Peter (Virchows Archiv, 1999)
The expression of epithelial mucins and Thomsen-Friedenreich-related antigens in preneoplastic and neoplastic hepatocellular lesions was systematically investigated using an in situ immunohistochemical staining approach.
Gesehen am 18.02.2019